Evaluation of the Effect of Microbiological Biopreparations On Seed Germination - Tog`ayeva, Muhayyo (Центр Научных Публикаций (buxdu.uz), 2023)
In the article Chlorella compared to the microalgae belonging to the generation, which is carried out somewhat quickly Botryococcus, Chlorococcum, Tetradesmus Scenedesmus detailed information on the identification of bioregulatory properties of strains belonging to the genus in the growth of plants